Candidiasis in Malignancy - Diany N Taher; Ari Fahrial Syam; Murdani Abdullah; Jumhana Atmakusuma; Khie Chen (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Esophageal candidiasis presents with a range of clinical findings and is rarely found among immunocompetent patient without predisposing factors. Between 20-50% of patient may be asymptomatic. One of predisposing factor of candidiasis is immunocompromised condition due to malignancy. Dysphagia is the most frequently presented feature of esophageal carcinoma. We demonstrated a case of esophageal candidiasis as one of early clinical presentation in patient with esophageal carcinoma. Keywords: esophageal candidiasis, esophageal carcinoma